ChemInform Abstract: Water‐Soluble Calix[4]arene Derivatives: Binding Stoichiometry and Spectroscopic Evaluation of the Host‐Guest Recognition Mechanism. Issue 49 (3rd December 2013) - Nimse, Satish Balasaheb; Song, Keum‐Soo; Kim, Taisun
Abstract Review: 64 refs.